1976
DOI: 10.1530/acta.0.0820691
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Canine Prolactin by Polyacrylamide Gel Electrophoresis

Abstract: The electrophoretic mobility of prolactin obtained from canine pituitary extract was studied with the aid of polyacrylamide disc electrophoresis. Using a preparative gel electrophoretic system the immunoreactive material was purified on a quantitative scale which was then used to develop a homologous radioimmunoassay for canine prolactin. The radioimmunoassay system was able to detect prolactin in the plasma of dogs after the administration of agents which would be expected to affect prolactin secretion.Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1978
1978
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…Canine and ovine PRL are similar in molecular size, amino acid composition, physical properties and biological activity (27)(28)(29), and ovine PRL has been shown to stimulate canine mammary tissue (30), as well as P secretion in the present study. Therefore, it is unlikely that the failure of ovine PRL to stimulate Rlx production is due to a species incompatability.…”
Section: Weeks Of Pregnancysupporting
confidence: 62%
“…Canine and ovine PRL are similar in molecular size, amino acid composition, physical properties and biological activity (27)(28)(29), and ovine PRL has been shown to stimulate canine mammary tissue (30), as well as P secretion in the present study. Therefore, it is unlikely that the failure of ovine PRL to stimulate Rlx production is due to a species incompatability.…”
Section: Weeks Of Pregnancysupporting
confidence: 62%
“…During pregnancy the progesterone concentrations remain maximal up to about Day 35 before waning steadily to give basal levels by the time of parturition or during the early stages of lactation (Austad, Lunde &Sjaastad, 1976;Concannon et al, 1975;Hadley, 1975 b;Smith & McDonald, 1974;Jones, Boyns, Bell, Christie & Parkes, 1973c;Masken, 1972;Christie, Bell, Horth & Palmer, 1971 ;Bell, Christie & YoungLai, 1971). Jones et al (1976) found increased plasma prolactin levels on the last day of pro-oestrus, but we were unable to find any clear changes in serum prolactin concentrations with thestageof the cycle. This was probably due to the times of blood sampling which were not frequent enough to detect shortterm hormonal changes around ovulation.…”
Section: Pregnancycontrasting
confidence: 55%
“…As found by Jones et al (1976) andGraf et al (1977) serum prolactin concentrations increase steadily during the last half of pregnancy and reach high concentrations during early lactation. The present study supplements these findings and shows that during the later stages of lactation, from about Day 84 onwards (related to the first day of copulation), prolactin levels waned steadily until cessation of lactation.…”
Section: Pregnancymentioning
confidence: 63%
See 1 more Smart Citation
“…Our group also previously showed that most of the cPRL activity remained in the precipitate [31]. This PRL-rich fraction can be efficiently used for further purification [30,32,33]. Con A Sepharose affinity chromatography was used as the first step in the isolation of cLH, cFSH and cTSH from the supernatant fluid.…”
Section: Discussionmentioning
confidence: 99%